FRI0212 Comparative effectiveness of first-line biologic monotherapy in rheumatoid arthritis. (15th June 2017) - Silvagni, E; Bortoluzzi, A; Carrara, G; Govoni, M; Scirè, C
Abstract : Background: Non-Biological disease modifying antirheumatic drugs (csDMARDs) are recommended in association to biologics (bDMARDS) in the treatment of Rheumatoid Arthritis (RA) and combination therapy is superior than bDMARD monotherapy with a better drug survival. Limited data are available in literature about the best biological treatment choice when a monotherapy is necessary in biologic-naïve patients. Objectives: To assess comparative effectiveness (drug survival) of different first-line bDMARDs when administered in monotherapy in a large population-based sample of RA deriving from the administrative health database of the Lombardy region in Italy. Methods: Data were obtained from health database of the Lombardy Region between 1/1/2004 and 31/12/2013. Patients with RA, diagnosed by a rheumatologist, with a certified diagnosis (exemption code 006.714.0) and treated with first-line approved bDMARDs (Abatacept [ABA], Adalimumab [ADA], Certolizumab [CTZ], Etanercept [ETA], Golimumab [GOL], Infliximab [INF] and Tocilizumab [TCZ]) were included; the presence of a combination therapy of any duration with a concomitant csDMARD (Methotrexate, Leflunomide, Sulfasalazine, Cyclosporine and Hydroxychloroquine) was compared to monotherapy. Clinical characteristics recorded were age, sex, disease duration, Charlson Comorbidity Index, hospitalization for bacterial infections, use of concomitant glucocorticoid (GCs) or Nonsteroidal Anti-Inflammatory Drugs (NSAIDs). Propensity to treatment with monotherapy was assessed by logistic models and results were presented as odds ratios and 95%confidence intervals (CI) Effectiveness was evaluated as drug survival using Cox proportional hazard models. Results are presented as hazard ratios (HR) and CI, crude and adjusted for pre-specified confounders. Results: 4478 RA patients who started a first-line bDMARD were included; 840 (18.8%) in monotherapy and 3638 (81.2%) in association to at least one csDMARD. Among biologic-naïve monotherapy patients, N.398 (47.4%) received ETA, N.215 (25.6%) ADA, N.92 (10.9%) INF, N.48 (5.7%) TCZ, N.35 (4, 2%) ABA, N.30 (3, 6%) CTZ, N.22 (2, 6%) GOL. Median survival on treatment was 19.9 months (7.9–45.1). Monotherapy was associated with a lower age, longer disease duration, a consistently higher Charlson Comorbidity Index (in particular hepatic or renal disease), lower GCs and NSAIDs intake. Compared to monotherapy, combination therapy was associated with a lower drug failure (crude HR 0.75 [95% CI 0.68–0.82]; adjusted HR 0.78 [95% CI 0.70–0.86]; p<0.0001). In patients in monotherapy, considering ETA as reference and adjusting for the above mentioned clinical characteristics, the HR for bDMARD failure was 1.32 for ADA (95% CI 1.07–1.63) and 2.38 for INF (95% CI 1.85–3.07). Conclusions: Monotherapy with bDMARDs is consistenly associated with lower retention rate in first-line therapy for anti-TNF drugs. Comparing bDMARDs administered in monotherapy, INF and ADA show a higher risk of withdrawal than ETA. Real life data support the currently recommended use of bDMARDs in association to csDMARDs. References: Souto et al. Rheum (Oxford)2016;55(3):523–34. Choy et al. Rheum (Oxford)2016; 21. Acknowledgements: None declared. Disclosure of Interest: None declared